Primitive neuroectodermal tumour of the lung with pericardial extension: a case report - Mohd Shah, Azarisman Shah; Abdullah, Aszrin; Maskon, Oteh; Mohamed, Zamri; Abdul Malek, Puteri Melor; Saidin, Noorfaizan (Elsevier, 2007)
A 16-year-old student-presented with a 4-week-history of progressive shortness of breath, loss of appetite and occasional blood-tinged sputum. The chest X-ray revealed massive right-sided pleural effusion with cardiomegaly. An echocardiogram revealed a large pericardial mass with massive pericardial effusion. Subsequent computed tomography of the thorax revealed a large heterogeneous mass in the right lung with extension into the pericardium. Lung biopsy revealed primitive neuroectodermal tumor (PNET) with small round blue cells, Homer-Wright rosettes, and CD99 positivity. We discuss pericardial metastases of PNET and its implication in this patient.